OCM seminativi: tendenze evolutive e assetto territoriale - Casini, Leonardo (Strumenti per la didattica e la ricerca, 2004)
The volume presents a key to understanding the current distribution of arable lands in Italy (based on an analysis conducted on 1994-1997 data) in relation to community disciplines and future prospects. In Italy, on over 14 million hectares of UAA (Usable Agricultural Area), about 57% is characterised by arable land. The importance of these crops, in addition to this visible global figure, is also confirmed at the level of individual production structures. In the short-term future, however, it is the arable lands that will be fully affected by the need to reduce surpluses and by the issues related to the environmental sustainability of production systems.